Sleep and circadian rhythm disturbance in kidney stone disease: a narrative review - He, Si-Ke; Wang, Jia-Hao; Li, Tao; Yin, Shan; Cui, Jian-Wei; Xiao, Yun-Fei; Tang, Yin; Wang, Jia; Bai, Yun-Jin (Frontiers in Endocrinology, 2023)
The circadian rhythm generated by circadian clock genes functions as an internal timing system. Since the circadian rhythm controls abundant physiological processes, the circadian rhythm evolved in organisms is salient for adaptation to environmental change. A disturbed circadian rhythm is a trigger for numerous pathological events. Recently, accumulated data have indicated that kidney stone disease (KSD) is related to circadian rhythm disturbance. However, the mechanism between them has not been fully elucidated. In this narrative review, we summarized existing evidence to illustrate the possible association between circadian rhythm disturbance and KSD based on the epidemiological studies and risk factors that are linked to circadian rhythm disturbance and discuss some chronotherapies for KSD. In summary, KSD is associated with systemic disorders. Metabolic syndrome, inflammatory bowel disease, and microbiome dysbiosis are the major risk factors supported by sufficient data to cause KSD in patients with circadian rhythm disturbance, while others including hypertension, vitamin D deficiency, parathyroid gland dysfunction, and renal tubular damage/dysfunction need further investigation. Then, some chronotherapies for KSD were confirmed to be effective, but the molecular mechanism is still unclear.